Verbal Working Memory in Schizophrenia: Relationship to Cigarette Smoking and Psychopathology - Hamzah, Hazura; Abdullah, Wan Norhaida Wan; Jamaluddin, Ruzita; Othman, Zahiruddin (Malaysian Psychiatric Association, 2012)
A number of researches suggest smoking serves as a form of self-medication to reduce the side effects of antipsychotic medications, to alleviate negative symptoms, and/or to ameliorate a number of cognitive deficits associated with schizophrenia. Objective: The aim of this study was to investigate the association of cigarette smoking with verbal working memory and psychopathology of patients with schizophrenia. Methods: Fifty-three patients with schizophrenia were assessed by a single rater using the Malay Version of Auditory Verbal Learning Test (MVAVLT) and Positive and Negative Syndrome Scale (PANSS). Smokers (n=30) were compared with nonsmokers (n=23) on socio-demographic, clinical, psychopathology and verbal memory variables. Single linear and multiple regression analysis were performed to determine factors associated with verbal memory performance. Results: Verbal working memory performance is associated with lower number of admission to ward, lesser severity of the negative symptoms or general psychopathology of schizophrenia and use of atypical antipsychotics in all schizophrenic subjects. Smokers with schizophrenia scored higher than non- smoker in measures that reflect immediate memory, delayed recall and recognition memory. However, the association between verbal working memory performance and smoking status was found to be not significant. Conclusion: Verbal working memory performance is associated with negative symptoms but not positive symptoms. This study failed to detect association of smoking on verbal working memory.